A simple configuration of beam steering substrate integrated waveguide aperture antenna loaded with metamaterials. Issue 4 (31st December 2021) - Cai, Yang; Li, Sen; Wu, Tao; Cao, Yufan
Abstract: This letter presents a novel broadband substrate integrated waveguide aperture antenna with simple structure and beam steering performance. By using the left‐hand and band gap characteristics of the mushroom‐shaped metamaterials, the main beam of the substrate‐integrated waveguide aperture antenna can be easily switched between the back‐fire and boresight directions. Above all, the beam scanning characteristic does not depend on three‐dimensional structures or complex loaded structures, therefore it is a promising technology for designing planar two dimensional beam steering array. Experimental results indicate that the impedance bandwidth of the antenna covers the frequency range from 13.3 to 16.7 GHz and the relative bandwidth is 22.7%. The accordance between the simulated and measured E‐plane radiation pattern of the antenna at three representative frequencies verifies the beam steering capability of the proposed antenna.